Atopic dermatitis and atopic march: which link? - Maiello, Nunzia; Giannetti, Arianna; Ricci, Giampaolo; Cinicola, Bianca; Carello, Rossella; Indolfi, Cristiana; Caffarelli, Carlo; Marseglia, Alessia; Calvani, Mauro; Miraglia del Giudice, Michele; Galli, Elena (Acta Biomedica Atenei Parmensis, 2021)
There is a long standing debate on the atopic march in childhood. The natural progression of allergic manifestations may be considered as comorbidities, which occur more frequently in a specific evolutive age. On the other hand, the natural history of allergies in children may follow trajectories that may be heterogeneous. The effects of atopic march in clinical practice have also been reported.